1994
DOI: 10.1002/pros.2990250307
|View full text |Cite
|
Sign up to set email alerts
|

PR92 antigen in human prostate fluid: Elevated levels in prostate cancer

Abstract: In this preliminary study, we report that an enzyme-linked immunofluorescence assay (EFLA) was developed for the determination of PR92 antigen in prostatic fluid, utilizing anti-PR92 monoclonal antibody. Fluid samples from 64 patients were assayed. PR92 antigen was expressed as unit per microgram (U/microgram) of prostatic fluid proteins. One hundred percent of men (7 out of 7) less than 50 years of age demonstrated concentrations less than 25 U/micrograms; 91% of men (10 out of 11) with documented carcinoma, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
1999
1999

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…However, only 1 (1%) of 79 serum specimens from age-matched men with no evidence of prostate cancer had an elevated level of PR92. Recently, an enzyme-linked immunofluorescence assay (ELIFA) has been developed to measure PR92 level in prostatic fluid by using PR92 mAb [108]. In this study, it was found that normal controls, BPH patients, high-risk patients (for prostate cancer), and prostate cancer patients had progressively increasing levels of PR92 in the prostatic fluid [108].…”
Section: Pr92mentioning
confidence: 88%
See 1 more Smart Citation
“…However, only 1 (1%) of 79 serum specimens from age-matched men with no evidence of prostate cancer had an elevated level of PR92. Recently, an enzyme-linked immunofluorescence assay (ELIFA) has been developed to measure PR92 level in prostatic fluid by using PR92 mAb [108]. In this study, it was found that normal controls, BPH patients, high-risk patients (for prostate cancer), and prostate cancer patients had progressively increasing levels of PR92 in the prostatic fluid [108].…”
Section: Pr92mentioning
confidence: 88%
“…Recently, an enzyme-linked immunofluorescence assay (ELIFA) has been developed to measure PR92 level in prostatic fluid by using PR92 mAb [108]. In this study, it was found that normal controls, BPH patients, high-risk patients (for prostate cancer), and prostate cancer patients had progressively increasing levels of PR92 in the prostatic fluid [108]. The mean value of PR92 in the prostatic fluid for the cancer group was significantly greater than that of all three other groups.…”
Section: Pr92mentioning
confidence: 99%